Ien van de Heuvel spreekt op partijcongres in 1977. Met microfoons. En foto's van partijraad op 4 juni 1977 - Morelis, Nick
Ien van de Heuvel spreekt op partijcongres in 1977. Met microfoons. En foto's van partijraad op 4 juni 1977.